INVISIBLE LABORATORY OF UNIVERSITY LECTURER’S MENTAL WORK - Alevtina S. Robotova (Высшее образование в России)
The author presents her own opinion on the university lecturer activities. The paper emphasizes the integrative character of university lecturer activities, which includes, besides teaching, research work, scientific guidance and consulting, membership in different councils and editorial boards, peer reviewing, and writing of articles, monographs, textbooks, and courses. Some kinds of his activities are unobvious and imperceptible. The author uses the metaphor “invisible laboratory of mental work” and expresses concern in connection with the uncertain position of a university teacher in the modernization processes in higher education and with possible loss of the value of a unique personality.